CHILD FRIENDLY PRINCIPLES BASED ON JUSTICE IN CHILD DEVELOPMENT INSTITUTION TANGERANG-INDONESIA - Fransiska Novita Eleanora; Irmanjaya Taher; Dwi Seno Wijanarko; Edy Supriyanto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Children as offenders of criminal acts are often untreated humanely or even lack sufficient attention to their rights as human beings and as the next generation of a nation. Since all people are equal before the law, acts of discrimination, violence, and intimidation should be prohibited. During their development in the institution, they must obtain justice and fulfill their rights, especially the right to life. This paper discusses the application of children’s rights before and after the formation or establishment of Lembaga Pidana Khusus Anak (LKPA) or Child Development Institution in Tangerang. On the LKPA, the law enforcement officials prioritize children’s rights and seek the best interests of children by implementing child-friendly principles. Children should be untried as adults. The law system should not perceive the child as an object but rather as a subject and conducting the self-development to them. It can help them realize the wrongdoing of their action and also produces a deterrent effect. This is since the instability of a child, mentally and psychologically, could trigger them to perform the criminal act. Sanctions do not mean they must be treated inhumanely, rather their rights must be protected legally. This includes their rights on education, health, law protection, as well as skills development, and other rights. If doing so, it can benefit not only for themselves but also for the community or other people. The research method used is through field observations by conducting direct interviews to the respondents involved to explain the remaining problems.